British cinema is undead: American horror, British comedy and generic hybridity in Shaun of the Dead. Issue 1 (2nd January 2016) - Decker, Lindsey
Abstract: This article examines the relationship between genre hybridity, British film culture and discourses of Americanization through British director Edgar Wright's financially successful and critically acclaimed horror-comedy film Shaun of the Dead (2004). The film both narratively and visually cites American director George Romero's original Dead trilogy (1968's Night of the Living Dead, 1978's Dawn of the Dead and 1985's Day of the Dead ), positioning itself within the zombie horror subgenre. However, much of the comedic narrative tropes in Shaun draw on common British comedic practices from WWII-era Ealing comedies, television two-man comedy teams and the Monty Python sketch troupe. The film enacts what I call transnational genre hybridity: the hybridity of the film's genre is also a hybridity of nation. The film also responds to cultural discourses around the service economy and post-Blair-era masculinity; in doing so, the film knowingly positions itself as part of British national cinema, which has often been seen as a cinema that engages with contemporary social issues. Through its specifically transnational generic hybridity, Shaun of the Dead situates itself across nations, which allows the film to comment upon the relationship between the American and British film industries and critique anti-Americanization discourses within British film culture